"Granulocytic sarcoma of cervical lymphnode: A diagnostic challenge". (2016) - Das, Hemlata; Hansa, Jagadish; Sahu, Mahesh Chandra; Padhy, Rabindra Nath
Abstract: Introduction: Granulocytic sarcoma is an event associated with acute or chronic myeloid leukemia in which, the extramedullary site consists of myeloid blasts and/or immature myeloid cells. Primary granulocytic sarcoma becomes a diagnostic challenge especially in the absence of cited hematological disorder or when lymphnode becomes an extramedullary with remote co-incidence. Presentation of case: This is a case of granulocytic sarcoma in a 15-year-old girl, who presented with a mass in the right side of neck, along with progressive dysphagia and aphasia. Histomorphologic diagnosis of the tissue was supported by immunohistochemical study with Avidin-biotin-peroxidase complex technique that was performed on formalin fixed tissue from the patient. Discussion: The clinicopathologic diagnosis remains an elusive decision with a malignant lymphoma, because of the isolated cervical mass presentation. Moreover, the patient was hemodynamically stable without the presence of any leukemic blast cell in the peripheral blood. Conclusion: Immunohistochemical study of the tissue from the neck mass helped to reach a correct diagnosis. The diagnosis was further reconfirmed on bone marrow trephine biopsy. A final trial with myeloid panel markers was the last alternatives to all differential diagnosis to round cell tumor. Tumor cells were immunoreactive to CD68, CD34, CD117 and myeloperoxidase, suggesting myeloid sarcoma.